2003
DOI: 10.2114/jpa.22.129
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combined Aerobic and Resistance Exercise Training on Abdominal Fat in Obese Middle-aged Women

Abstract: The purpose of this study was to investigate the effect of combined aerobic and resistance training on abdominal fat. Our participants in the study consisted of thirty obese women. They were separated into three groups: a control group (n=10), an aerobic training group (n=10) and a combined training group (n=10). The aerobic training group was composed of 60-70% HRmax (intensity), 60 minutes a day (duration) for 6 days a week (frequency). The combined training group was separated into resistance training (3 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
90
0
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 21 publications
12
90
0
12
Order By: Relevance
“…Furthermore, it has been shown that SRT preferentially mobilizes the visceral and subcutaneous adipose tissue in the abdominal region [31, 6 38,61,105]. This kind of training procedure improves insulin-stimulated glucose uptake in patients with impaired glucose tolerance or T2D [41].…”
Section: Physical Activity Programmesmentioning
confidence: 99%
“…Furthermore, it has been shown that SRT preferentially mobilizes the visceral and subcutaneous adipose tissue in the abdominal region [31, 6 38,61,105]. This kind of training procedure improves insulin-stimulated glucose uptake in patients with impaired glucose tolerance or T2D [41].…”
Section: Physical Activity Programmesmentioning
confidence: 99%
“…There is Efficacy of exercise for treating overweight in youth E Atlantis et al sufficient evidence in adult studies to show that reductions in central obesity can be seen following either aerobic 94,95 or weight-training 96 exercise without weight loss, whereas combined aerobic and weight-training exercise is more effective than aerobic exercise alone, 97 and exercise plus dietary restriction is more effective than dietary restriction alone. 98 As in adults, excessive visceral fat (central obesity) is associated with an increased disease risk in children and adolescents, particularly for components of the 'metabolic syndrome.'…”
Section: Central Obesitymentioning
confidence: 99%
“…With moderate intensity exercise during 60 minutes, we consider that the most amount of energy expenditure occurs during exercise and few amount later at resting. The strength training proposed to obese might leads to increase of lean body mass, muscle strength and power in one hand and decrease of body fat percentage, waist circumference, visceral and subcutaneous abdominal and thigh fat thickness on the other hand [49] [50] [51] [52]. Interestingly, it has also been found that the resting metabolism is higher after strength training than endurance training with low or moderate intensity [41] .This mean that strength training that we combined with moderate endurance training will increase the low amount of fat oxidation post exercise due to the moderate endurance training.…”
Section: Effect Of Time-of-day Specific Obese Training On Body Composmentioning
confidence: 99%